Nuclear Structure Studies with Stable and Radioactive Beams: The SPES radioactive ion beam project. (March 2015) - de Angelis, G; Prete, G; Andrighetto, A; Manzolaro, M; Corradetti, S; Scarpa, D; Rossignoli, M; Monetti, A; Lollo, M; Calderolla, M; Vasquez, J; Zafiropoulos, D; et al.
Abstract: A new Radioactive Ion Beam (RIB) facility (SPES) is presently under construction at the Legnaro National Laboratories of INFN. The SPES facility is based on the ISOL method using an UCx Direct Target able to sustain a power of 10 kW. The primary proton beam is provided by a high current Cyclotron accelerator with energy of 35-70 MeV and a beam current of 0.2-0.5 mA. Neutron-rich radioactive ions are produced by proton induced fission on an Uranium target at an expected fission rate of the order of 10 13 fissions per second. After ionization and selection the exotic isotopes are re-accelerated by the ALPI superconducting LINAC at energies of 10A MeV for masses in the region A=130 amu. The expected secondary beam rates are of the order of 10 7 – 10 9 pps. Aim of the SPES facility is to deliver high intensity radioactive ion beams of neutron rich nuclei for nuclear physics research as well as to be an interdisciplinary research centre for radio-isotopes production for medicine and for neutron beams.